Rekrutmen Pelayan Yang Ideal Menurut Kisah Para Rasul 6:3 - Widi Prasetyo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
This article discusses the recruitmen servant of God in the church to see the background of the election of the seven deacon were chosen from Acts 6:3 with focus on the requirement: 1. Famous either; 2. Full of the spirit; 3. Full of wisdom. And do not overlook about Biblical selection procedures. And considering the impact of recruitment for evangelism and church growth.Keywords: transition time,leadership, Christian institution.